Reconstructing Shared Responsibility for Refugee Education under ARSIWA - Ricky Primanda Ikrar Abadi (Indonesian Journal Publisher, 2026)
This study examines the growing challenges in ensuring refugees’ right to education within the current international legal framework. As the number of displaced persons continues to increase globally, the existing system largely based on territorial responsibility has proven insufficient in addressing the needs of refugee populations, particularly in transit countries with limited capacity.This research aims to rethink how state responsibility is distributed by using the framework of the Articles on Responsibility of States for Internationally Wrongful Acts (ARSIWA), combined with international human rights obligations. Using a normative legal approach and literature-based analysis, this study explores how responsibility can be shared among states based on both their contribution to displacement and their institutional capacity. The findings suggest that a purely proximity-based model is inadequate. Instead, a shared responsibility approach where sending, transit, and receiving states all play distinct roles—offers a more balanced and realistic solution. By reinterpreting ARSIWA, particularly provisions related to aid and assistance, this study argues that responsibility should extend beyond territorial borders. This approach not only contributes to legal scholarship but also provides a more practical foundation for developing fairer international policies on refugee education.